Effects of GSK-3 inhibition on LPS-induced neuroinflammation and IL-10 production in microglia - Md Zain, Zuhaida (2016)
Microglia are resident macrophages of the central nervous system (CNS) that play a role in the immune surveillance system against various pathogenicities. However, excessive inflammation resulting from activation of microglia has been implicated in the neurodegenerative diseases such as multiple sclerosis. The protein kinase, Glycogen Synthase Kinase (GSK) 3, is involved in many cellular functions including microglial activation. Previously, inhibition of GSK-3 has been shown to reduce inflammation due to decreased production of pro-inflammatory cytokines and increased production of IL-10 in LPS-induced endotoxin shock animal model. Thus, this study was performed to elucidate the possible immunoregulatory effects of GSK-3 inhibitors on activated microglia. We hypothesized that inhibition of GSK-3 would reduce the exaggeration of inflammation in LPS-induced microglial activation with associated increased of IL-10 production. The optimal concentration of LPS and incubation period were optimized and determined by measuring the level of nitric oxide (NO) produced by BV-2, microglia cell lines, without compromising their effect on cell viability. The GSK-3 inhibitors, including lithium chloride (LiCl), SB216763, NP12 and CHIR99021 were used to block GSK-3 activities in the BV-2 cells. All GSK-3 inhibitors tested have shown their efficacy in reducing production of proinflammatory molecules, such as NO, glutamate, MCP-1 and cytokines (TNF- α and IL-6). Interestingly, reduction of pro-inflammatory molecules via GSK-3 inhibition was associated with significant increase in IL-10 production. Furthermore, treatment with GSK-3 inhibitor reduced expression of microglial activation markers, CD11b, while increased expressions of microglial inhibitory markers, CD200R, which confirmed the ability of GSK-3 inhibitor in inhibiting microglial activation. These results indicate that GSK-3 inhibitors effectively reduced pro-inflammatory molecules via inhibition of microglial activation. Moreover, these inhibitors could potentially reduce the severity of neuroinflammation by enhancing IL-10 production.